Contemporary Challenges for Cloud Computing Data Governance in Information Centers: An analytical study - عبد الحسن عامر عبد الرزاق; توفيق احمد زهير (Journal of Economics and Administrative Sciences, 2019)
Purpose – The Cloud computing (CC) and its services have enabled the information centers of organizations to adapt their informatic and technological infrastructure and making it more appropriate to develop flexible information systems in the light of responding to the informational and knowledge needs of their users. In this context, cloud-data governance has become more complex and dynamic, requiring an in-depth understanding of the data management strategy at these centers in terms of: organizational structure and regulations, people, technology, process, roles and responsibilities. Therefore, our paper discusses these dimensions as challenges that facing information centers in according to their data governance and the impacts on the effectiveness of their information systems. Design/methodology/approach – A comparative approach was used to identify the most important contemporary challenges that faced by ICT centers in Iraqi universities with regard to adopting the governance of cloud computing. Also, we designed an electronic survey questionnaire with indicators in the context of study variables to collect data and information from study population (public and private Iraqi universities) and analyze the collect data using structural equation modeling in (SPSS; AMOS v.25). Findings – The study found a direct and indirect positive and significant impact of applying the cloud data governance and overcoming their challenges on reinforcing the effectiveness of information systems. Research limitations/implications – The research discuss its issues at the information centers in a sample of Iraqi universities in the governmental higher education sector in Iraq. Practical implications – The most important implications of paper are giving a deeper understanding to the administrators of CC at Iraqi universities to maximize their benefits and this show our paper value. Social implications – no implications. Originality/value – Contributes to develop a road map to adopt the concepts of governance and IT governance like cloud computing governance in Iraqi universities. Paper type: Research paper.